2016
DOI: 10.1177/0706743716645286
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Canadian Psychiatry Residents: A National Survey

Abstract: Objective: Burnout is a serious problem for health care providers that has implications for clinical practice and personal health. While burnout is known to affect residents, no studies have examined the prevalence or impact of burnout among Canadian psychiatry residents. Method: Residents in all Canadian psychiatry training programs were surveyed between May 1, 2014, and July 1, 2014. The survey included a well-validated, single-item measure to assess symptoms of burnout, several demographic questions, and Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
50
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 21 publications
5
50
0
3
Order By: Relevance
“…This nding is consistent with many studies conducted among psychiatry residents included in a systematic review by Chan MK (23). For example, Kealy and colleagues (24) reported that burnout rates in program year (PGY)-2 and PGY-3 residents ranged from 27-31% compared with 16-18% in PGY-4 and PGY-5…”
supporting
confidence: 86%
“…This nding is consistent with many studies conducted among psychiatry residents included in a systematic review by Chan MK (23). For example, Kealy and colleagues (24) reported that burnout rates in program year (PGY)-2 and PGY-3 residents ranged from 27-31% compared with 16-18% in PGY-4 and PGY-5…”
supporting
confidence: 86%
“…Stressors include worries about high financial debt load, extended work hours, sleep deprivation, licensing exams, complex and challenging patient caseloads, repeated exposure to grief and loss, and harassment from staff physicians, allied health workers, patients, and even other residents in training. [4][5][6][7][8][9][10][11][12][13][14][15] Compounding these issues are the real and/or perceived fears related to social stigma, negative training evaluations, and jeopardized career opportunities that prevent residents from accessing psychological support/counselling services to help with the management of their personal and professional stress. 4,16 In some cases, this added stress burden leads to burnout.…”
Section: -7mentioning
confidence: 99%
“…Often, it manifests in poor academic performance and substandard patient care. [11][12][13][14][15][17][18] When this happens, residents are more likely to experience crises in professional identity development, situations where their actions do not match who they are or who they want to become. 19 These identity crises can reinforce feelings of fear, failure, lack of self-confidence, and lead to professional self-doubt.…”
Section: -7mentioning
confidence: 99%
“…2 Their correspondence raises the issue of the connection between burnout and depression, noting that our survey did not consider whether residents who indicated burnout symptoms may have indeed been depressed.…”
mentioning
confidence: 97%